Analisis Kawasan Rawan Bencana Longsor dan Mitigasi di Kecamatan Padang Selatan - Ibrahim, Malik; Triyatno, Triyatno (Lembaga Yasin AlSys, 2025)
South Padang District has varied topography with steep slopes, making it prone to landslides, particularly during the rainy season. This vulnerability is exacerbated by uncontrolled land-use changes, necessitating a comprehensive study to map hazard-prone areas and formulate mitigation strategies. This study aims to: (1) model landslide-prone areas in South Padang District using the Frequency Ratio (FR) method and (2) determine priority mitigation efforts using the Analytical Hierarchy Process (AHP) method. A descriptive quantitative approach was applied, with the FR method used to analyze hazard levels and AHP employed to establish mitigation strategy priorities. The analysis results indicate three hazard categories: low (26%, 208,524 pixels), medium (34%, 266,624 pixels), and high (40%, 379,864 pixels) of the total area. AHP analysis using Expert Choice placed landslide hazard mapping as the top priority with a weight of 0.376. These findings emphasize that spatial approaches and land-use control should form the basis for effective, targeted, and sustainable landslide mitigation policies.